Engineering Archeal Surrogate Systems for the Development of Protein–Protein Interaction Inhibitors against Human RAD51. Issue 23 (20th November 2016) - Moschetti, Tommaso; Sharpe, Timothy; Fischer, Gerhard; Marsh, May E.; Ng, Hong Kin; Morgan, Matthew; Scott, Duncan E.; Blundell, Tom L.; R. Venkitaraman, Ashok; Skidmore, John; Abell, Chris; Hyvönen, Marko
Abstract: Protein–protein interactions (PPIs) are increasingly important targets for drug discovery. Efficient fragment-based drug discovery approaches to tackle PPIs are often stymied by difficulties in the production of stable, unliganded target proteins. Here, we report an approach that exploits protein engineering to "humanise" thermophilic archeal surrogate proteins as targets for small-molecule inhibitor discovery and to exemplify this approach in the development of inhibitors against the PPI between the recombinase RAD51 and tumour suppressor BRCA2. As human RAD51 has proved impossible to produce in a form that is compatible with the requirements of fragment-based drug discovery, we have developed a surrogate protein system using RadA from Pyrococcus furiosus. Using a monomerised RadA as our starting point, we have adopted two parallel and mutually instructive approaches to mimic the human enzyme: firstly by mutating RadA to increase sequence identity with RAD51 in the BRC repeat binding sites, and secondly by generating a chimeric archaeal human protein. Both approaches generate proteins that interact with a fourth BRC repeat with affinity and stoichiometry comparable to human RAD51. Stepwise humanisation has also allowed us to elucidate the determinants of RAD51 binding to BRC repeats and the contributions of key interacting residues to this interaction. These surrogate proteins have enabled the development of biochemical and biophysical assays in our ongoing fragment-based small-molecule inhibitor programme and they have allowed us to determine hundreds of liganded structures in support of our structure-guided design process, demonstrating the feasibility and advantages of using archeal surrogates to overcome difficulties in handling human proteins. Graphical Abstract: Highlights: Archeal RadA, humanised to resemble RAD51, binds the fourth BRC repeat with high affinity. Chimeric archeal/human RAD51 shows increased thermal stability. Robust crystallographic system enables fragment-based drug discovery against RAD51. Dedicated surrogate proteins were needed for different assays.